2022
DOI: 10.3390/antiox11050818
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative-Induced Angiogenesis Is Modulated by Small Extracellular Vesicle miR-302a-3p Cargo in Retinal Pigment Epithelium Cells

Abstract: Extracellular vesicles are released from cells under diverse conditions. Widely studied in cancer, they are associated with different diseases playing major roles. Recent reports indicate that oxidative damage promotes the release of small extracellular vesicle (sEVs) from the retinal pigment epithelium (RPE), with an angiogenic outcome and changes in micro-RNA (miRNA) levels. The aim of this study was to determine the role of the miRNA miR-302a-3p, included within RPE-released sEVs, as an angiogenic regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Under these conditions, HUVEC cells were unable to produce tubes and branches [91]. In a similar approach, we transfected ARPE-19 cells with a miR-302a-3p mimic and compared the effect of adding sEVs obtained from these cells to HUVEC on tube and vessel formation, with the effect of sEVs from ARPE-19 cells incubated with hydrogen peroxide, and confirmed that miR-302a-3p contained in sEVs can modify VEGFA mRNA expression levels as part of its antiangiogenic features [92]. These results strongly indicate the pivotal role of miRNAs as angiogenic modulators, especially under oxidative conditions.…”
Section: Micro Rnasmentioning
confidence: 69%
See 1 more Smart Citation
“…Under these conditions, HUVEC cells were unable to produce tubes and branches [91]. In a similar approach, we transfected ARPE-19 cells with a miR-302a-3p mimic and compared the effect of adding sEVs obtained from these cells to HUVEC on tube and vessel formation, with the effect of sEVs from ARPE-19 cells incubated with hydrogen peroxide, and confirmed that miR-302a-3p contained in sEVs can modify VEGFA mRNA expression levels as part of its antiangiogenic features [92]. These results strongly indicate the pivotal role of miRNAs as angiogenic modulators, especially under oxidative conditions.…”
Section: Micro Rnasmentioning
confidence: 69%
“…Furthermore, some miRNAs have been involved in eye-related vascular proliferation. Initially proposed as a hypothesis, that RPE derived sEVs and their miRNA content could be related to choroidal neovascularization in AMD [90] was relatively quickly confirmed in different experimental models [22,25,36,80,91,92]. Collectively identified as "angiomiR-NAs", they are expressed in endothelial cells, mir-126, mir-210, mir-221/222, among others, and are able to promote or repress angiogenesis (reviewed in [93]).…”
Section: Micro Rnasmentioning
confidence: 99%
“…sEVs from ARPE-19 cell medium were isolated using the total exosome isolation reagent from the cell culture medium (Thermo Fisher Scientific, Waltham, MA, USA), following the previously described protocol for matrigel and migration assay [35]. For immunofluorescence imaging and electron microscopy, sEVs were isolated through a series of centrifugation steps.…”
Section: Sevs Isolationmentioning
confidence: 99%
“…Oxidative stress : Inducing oxidative stress in parent cells through specific culture conditions presents another avenue to amplify sEV yields. Reportedly, the treatments of 80 nM ethanol 49 or 600 μM H 2 O 2 50 boosted the section of sEVs from retinal pigment epithelium cells (ARPE‐19). Moreover, the sEVs secreted under these conditions exhibited heightened expression of vascular endothelial growth factor receptors (VEGFR) on their membranes, along with increased VEGFR mRNA within their lumens.…”
Section: Improving the Yields Of Sevsmentioning
confidence: 99%
“…For example, the application of hypoxia‐pretreatment not only leads to increased yields of MSC‐derived sEVs but also augments the content of angiogenic and anti‐inflammatory cargoes, encompassing miRNAs and proteins 44–48 . Culturing ARPE‐19 in culture medium containing ethanol 49 or 600 μM H 2 O 2 50 was observed to upregulate the expression of VEGFR on the membrane and more VEGFR mRNA in the lumen of sEVs, thus affecting the angiogenesis of obtained sEVs. Such alterations affect the angiogenic potential of the resulting sEVs.…”
Section: Improving the Yields Of Sevsmentioning
confidence: 99%